ENVIRONMENTAL IMPLICATIONS CONCERNING THE CHEMICAL COMPOSITION AND PARTICLE DISTRIBUTION OF ANTI – SKID MATERIAL - MUNTEAN, Dana Florina; IVAN, Ilarie; MUREŞAN, Liana (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Anti-skid material (AM) used to improve the traffic conditions could affect the particulate matter emissions during winter. The investigated AM sample contains silica particles to improve the friction coefficient between tires and road surface and crystalline sodium chloride as anti-glaze agent. We also found some interesting rusty particles containing iron hydroxide (lepidocrocite and goethite) mixed with fine quartz sliver. Compression test shows that those particles have a low strength being able to disintegrate in harsh traffic conditions. The powder resulted after crushing of rusty particles feature fine fractions with diameter in the range of 1 – 10 μm. Such fractions were found in the collected sedimenting particles (SP) proving their ability to be suspended in atmosphere. The monitoring performed with Automatic Monitoring Air Quality Stations shows the average values for PM2.5; PM10 and SP are below the maximum accepted limit. However, the registered values were high on days with intensive car traffic and lower on other days. The situation could be improved by a proper sorting of rusty particles from re-circulated anti-skid material.